L’odeur de l’axé - Arnaud Halloy (Journal de la Société des Américanistes)
The Xangô Cult, as most Afro-American religions, is an “olfactive” religion, dealing with a large variety of smells, and among them intense smells, which are an integral part of its ritual activity. Curiously, such phenomenological blatancy has never caught much interest among Afro-Brazilianists. It might be ethnographically noticed here and there, but there are very few attempts, if any, of theorizing their potential ritual function. Drawing on the “olfactography” of the sacrificial rite of the Xangô Cult, my aim is to account for what smells do to rituals and the people who take part in them. I suggest three theoretical claims: the hypothesis of the metonymic function of smells (Howes 1987), i.e. that the very nature of smell—their liminal, intangible and evolutive character, as well as their privileged link to emotions—redouble at the experiential level the rituals’ symbolic function of transformation; the hypothesis of an “olfactive evaluative conditioning” (Zucco 2013) at the heart of the metonymic function of smells; the existence of olfactive practices and “styles,” which are constitutive elements of collective identities in Afro-Brazilian religions.